Determining The Social Media Usage Characteristics of School of Health Students In Professional Organizat Ions - Ergün, Gül; Keskin, Beste (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2019)
Objectives: This study is in the descriptive design and has been planned to determine social media use characteristics of school of health students in professional organizations. Study Design: The data were collected from 461 participants studying at a school of health in March 2016. The questionnaire form, prepared by the author and in comformance with literature, was used in collecting the data. Results: It was determined that 42.1% of the participants spent 3-4 hours on the Internet in a day. 77.4% of the participant students used social media for the purpose of research. 23% of them became members of a professional group through social media. Conclusion: The vast majority of students spend much time on social media. Social media use is high for a professional subject. In order to emphasize the importance of professional organization, it is recommended that seminars on efficient use of social media be organized at high schools or universities where education and training are provided on health. Additionally, the importance of social media use and being members of professional communities through social media should be emphasized in the curricula of vocational lessonsincluding deontology and interpersonal relations

Amaç: Tanımlayıcı nitelikte olan bu araştırma, sağlık yüksekokulu öğrencilerinin mesleki örgütlenmede sosyal medya kullanım özelliklerinin belirlenmesi amacıyla planlanmıştır. Çalışma Planı: Veriler 2016 mart ayında bir sağlık yüksekokulunda 461 kişi ile gerçekleştirilmiştir. Verilerin toplanmasında literatür doğrultusunda araştırmacılar tarafından oluşturulan anket formu kullanılmıştır. Bulgular: Katılımcıların %42.1’i internette günde 3-4 saat zaman geçirmiştir. Araştırmaya katılan öğrencilerin %77.4’ü araştırma yapmak için sosyal medyayı kullanmıştır. Katılımcıların %23’ü sosyal medya aracılığıyla mesleki bir gruba üye olmuşlardır. Sonuç: Öğrencilerin büyük çoğunluğu sosyal medyada fazla zaman geçirmektedir. Sosyal medyayı mesleki bir konu için kullanım oranları fazladır. Mesleki örgütlenmenin önemini vurgulamak için üniversitelerin sağlıkla ilgili eğitim veren okullarında sosyal medyanın etkin kullanımı üzerine seminerler verilmesini; sosyal medya üzerindeki mesleki topluluk, grup ve sayfalara üyeliğin öneminin deontoloji, kişilerarası ilişkiler ve diğer mesleki derslerin müfredatlarında yer verilmesi önerilmiştir
Sağlık Yüksekokulu Öğrencilerinin Mesleki Örgütlenmede Sosyal Medya Kullanım Özelliklerinin Belirlenmesi